FAKTOR DETERMINAN YANG BERHUBUNGAN DENGAN MOTIVASI KERJA PEGAWAI DI PUSKESMAS JUHAR KECAMATAN JUHAR KABUPATEN KARO - Felix Kasim; Astuti Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
The related factors that suspected to be employee motivation’s based on Frederick Herzberg's theory are intrinsic and extrinsic factors which consisting of achievement, reward, responsibility, work environment, superiors / subordinate communication, and supervision. The purpose of this research is to analyze the determinants of factors associated with employee motivation. This research is quantitative research with the survey is the method through an explanatory research approach. The research was conducted at Juhar Public Health Center, Karo District. The population of this research is 52 people and the sample is 52 people. Data analysis use univariate analysis, bivariate analysis with chi-square, and multivariate analysis use multiple logistic regression test. The results showed that factors related to employee motivation in Puskesmas Juhar, Juhar Sub-district, Karo Regency in 2018 were responsibility, subordinate-supervisor communication, and supervision, there was a significant correlation. The most dominant variable related to this research is the variable of responsibility and the value of PR = 9,122. Personnel responsible for their job has a high work motivation 9.1 times higher than irresponsible employees. Unrelated variables are achievement, reward and work environment. It is suggested to the irresponsible staff of public health center to better understand their duties and responsibilities as employees to be more motivated in working and program targets can be achieved.